Metrics for evaluation of automatic epileptogenic zone localization in intracranial electrophysiology - Hrtonova, Valentina; Nejedly, Petr; Travnicek, Vojtech; Cimbalnik, Jan; Matouskova, Barbora; Pail, Martin; Peter-Derex, Laure; Grova, Christophe; Gotman, Jean; Halamek, Josef; Jurak, Pavel; Brazdil, Milan; et al. (Clinical neurophysiology, 2025)
INTRODUCTION: Precise localization of the epileptogenic zone is critical for successful epilepsy surgery. However, imbalanced datasets in terms of epileptic vs. normal electrode contacts and a lack of standardized evaluation guidelines hinder the consistent evaluation of automatic machine learning localization models. METHODS: This study addresses these challenges by analyzing class imbalance in clinical datasets and evaluating common assessment metrics. Data from 139 drug-resistant epilepsy patients across two Institutions were analyzed. Metric behaviors were examined using clinical and simulated data. RESULTS: Complementary use of Area Under the Receiver Operating Characteristic (AUROC) and Area Under the Precision-Recall Curve (AUPRC) provides an optimal evaluation approach. This must be paired with an analysis of class imbalance and its impact due to significant variations found in clinical datasets. CONCLUSIONS: The proposed framework offers a comprehensive and reliable method for evaluating machine learning models in epileptogenic zone localization, improving their precision and clinical relevance. SIGNIFICANCE: Adopting this framework will improve the comparability and multicenter testing of machine learning models in epileptogenic zone localization, enhancing their reliability and ultimately leading to better surgical outcomes for epilepsy patients.
Keywords: Young Adult; Machine learning; Male; mladý dospělý; Epileptogenic zone; Adolescent; Adult; dospělí; Intracranial electroencephalography; mužské pohlaví; lidé středního věku; mladiství; elektrokortikografie; Evaluation metrics; Class imbalance; lidé; Machine Learning; ženské pohlaví; Drug Resistant Epilepsy; Humans; refrakterní epilepsie; strojové učení; Epilepsy; Female; Epileptogenic tissue localization; Electrocorticography; Binary classification; Seizure onset zone; Middle Aged